Akses Informasi dan Persepsi Mahasiswa Keperawatan terhadap Jasa Perpustakaan Jurusan Keperawatan Politeknik Kesehatan Surakarta - Harnanto, Addi Mardi (Jurusan Keperawatan FIKES UNSOED, 2008)
The objective of this study is to analyze the use and participant access behaviour on library services, perception on the services, collection, and its layout of the library unit in Jurusan Keperawatan, Poltekkes Surakarta. An assessment was conducted to 60 students as library members.The assessment was designed by using survey method with questionnaire as interview guidance. The result showed that information access of participants in using library services was low according to needed collection, reading activity, and library loan. Perception of participants on library collection and services was positive, especially on attitude of librarian, and library room setting and room comfortable. 25% of respondent require increasing the literature collection especially the literature in English.